Assessment of the Prevalence of Proactive Penicillin Allergy Testing in Patients Labeled as Penicillin Allergic in Dhanusadham District of Nepal: Assessment of the Prevalence of Proactive Penicillin Allergy Testing in Patients Labeled as Penicillin Allergic in Dhanusadham District of Nepal - Das, Dr. Rajesh Chandra (International Journal of Pharmaceutical & Biological Archive, 2019)
This study aims to promote penicillin allergy testing in an outpatient to penicillin allergy and educate both patients and clinicians about testing. Patients with a history of penicillin allergy were screened for penicillin allergy testing. The results of allergy testing and patient satisfaction after testing were the main outcomes. A total of 82 patients were recruited, although only 37 actually underwent testing. None of these 37 had a positive skin test and none of 36 had a positive oral challenge (one refused it). Following testing, 2 patients (5%) had subjective reactions within 24 h. Three (10%) were subsequently treated with a beta-lactam, and all reported that testing provided important information to their medical history. In conclusion, the penicillin allergy testing safely evaluates patients labeled as penicillin allergic. It is well tolerated and embraced by the patients who undergo testing. In our study, none of the patients tested had an allergic reaction, but we identified multiple barriers to developing a protocol for testing patients from the primary care setting.